Systemically Administered Brain-Targeted Nanoparticles Transport Peptides across the Blood—Brain Barrier and Provide Neuroprotection. Issue 3 (March 2015) - Yemisci, Muge; Caban, Secil; Gursoy-Ozdemir, Yasemin; Lule, Sevda; Novoa-Carballal, Ramon; Riguera, Ricardo; Fernandez-Megia, Eduardo; Andrieux, Karine; Couvreur, Partick; Capan, Yilmaz; Dalkara, Turgay
Although growth factors and anti-apoptotic peptides have been shown to be neuroprotective in stroke models, translation of these experimental findings to clinic is hampered by limited penetration of peptides to the brain. Here, we show that a large peptide like the basic fibroblast growth factor (bFGF) and a small peptide inhibitor of caspase-3 (z-DEVD-FMK) can effectively be transported to the brain after systemic administration by incorporating these peptides to brain-targeted nanoparticles (NPs). Chitosan NPs were loaded with peptides and then functionalized by conjugating with antibodies directed against the transferrin receptor-1 on brain endothelia to induce receptor-mediated transcytosis across the blood—brain barrier (BBB). Pre-ischemic systemic administration of bFGF- or z-DEVD-FMK-loaded NPs significantly decreased the infarct volume after 2-hour middle cerebral artery occlusion and 22-hour reperfusion in mice. Co-administration of bFGF- or z-DEVD-FMK-loaded NPs reduced the infarct volume further and provided a 3-hour therapeutic window. bFGF-loaded NPs were histologically detected in the brain parenchyma and also restored ischemia-induced Akt dephosphorylation. The neuroprotection was not observed when receptor-mediated transcytosis was inhibited with imatinib or when bFGF-loaded NPs were not conjugated with the targeting antibody, which enables them to cross the BBB. Nanoparticles targeted to brain are promising drug carriers to transport large as well as small BBB-impermeable therapeutics for neuroprotection against stroke.